Cellular nanovesicles for therapeutic immunomodulation: A perspective on engineering strategies and new advances - Endong Zhang; Philana Phan; Zongmin Zhao (Elsevier, 2023)
Cellular nanovesicles which are referred to as cell-derived, nanosized lipid bilayer structures, have emerged as a promising platform for regulating immune responses. Owing to their outstanding advantages such as high biocompatibility, prominent structural stability, and high loading capacity, cellular nanovesicles are suitable for delivering various immunomodulatory molecules, such as small molecules, nucleic acids, peptides, and proteins. Immunomodulation induced by cellular nanovesicles has been exploited to modulate immune cell behaviors, which is considered as a novel cell-free immunotherapeutic strategy for the prevention and treatment of diverse diseases. Here we review emerging concepts and new advances in leveraging cellular nanovesicles to activate or suppress immune responses, with the aim to explicate their applications for immunomodulation. We overview the general considerations and principles for the design of engineered cellular nanovesicles with tailored immunomodulatory activities. We also discuss new advances in engineering cellular nanovesicles as immunotherapies for treating major diseases.